A comparative evaluation of PID-based optimisation controller algorithms for DC motor - Ahamed S.R.; Parumasivam P.; Hossain Lipu M.S.; Hannan M.A.; Ker P.J. (Inderscience Publishers, 2023)
Controllers; DC motors; Electric control equipment; Particle swarm optimization (PSO); Proportional control systems; Three term control systems; Two term control systems; Backtracking search algorithms; Comparative analysis; Comparative evaluations; Controller algorithm; Industrial activities; Optimum parameters; Particle swarm optimisation; Proportional integral derivative controllers; Electric machine control